Typological Analysis Of Cultural Heritage Objects In Uzbekistan In Different Periods. (Eurasian Journal of Humanities and Social Sciences, 2024)
This article reveals the typological analysis, general connection, and development of historical architectural objects and archaeological monuments built in different periods, which distinguish them from other countries with many historical monuments built on the territory of Uzbekistan.